1974
DOI: 10.1093/ajcn/27.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium interrelationships in ischemic heart disease: a review

Abstract: Cummings and Clark (4) Cummings (3) Rigo et al. (5) INTERRELATIONSHIPS IN HEART DISEASE 61 a Coronary ligation. b Ringer's solution without Mg. C Two milliequivalents Mg in 5% dextrose. water to the calcium and magnesium intakes of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(84 citation statements)
references
References 107 publications
2
81
0
1
Order By: Relevance
“…The theory of Seelig and Heggtveit states that the magnesium deficient status and an altered electrolyte concentration are caused by the reduction of the Na/K ATPase activity, leading to sodium accumulation in the cardiac myocytes. Elevated myocardial sodium levels would result in the reversal of the Na+/k+ exchange and a rise in the intracellular calcium levels [19].This intracellular shift in calcium decreases the ionized calcium levels in the serum. This explains the electrical instability in the hearts of magnesium deficient individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The theory of Seelig and Heggtveit states that the magnesium deficient status and an altered electrolyte concentration are caused by the reduction of the Na/K ATPase activity, leading to sodium accumulation in the cardiac myocytes. Elevated myocardial sodium levels would result in the reversal of the Na+/k+ exchange and a rise in the intracellular calcium levels [19].This intracellular shift in calcium decreases the ionized calcium levels in the serum. This explains the electrical instability in the hearts of magnesium deficient individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Magnesium de®ciency can also lead to increased platelet aggregation (Hwang et al, 1993). It has also been linked epidemiologically with increased risk for diabetic retinopathy (McNair et al, 1978) and ischaemic heart disease (Seelig et al, 1974). Choice of oral hypoglycaemic agents may affect magnesium handling: biguanide usage is linked with hypomagnesaemia, whereas glipizide raises serum magnesium (McBain et al, 1988).…”
Section: Magnesiummentioning
confidence: 99%
“…Experimental and clinical evidence suggest that magnesium (Mg2') deficiency, in animals and man, could be a significant factor in the aetiology of several cardiovascular disease states (Seelig & Heggtveit, 1974;Burch & Giles, 1977;Altura, 1979;Altura 1980;Altura & Altura, 1981). In a recent in vitro strudy, we demonstrated that acute withdrawal of magnesium induces contractile responses in canine coronary arteries (Turlapaty & Altura, 1980).…”
Section: Litroductionmentioning
confidence: 99%